A Prototype of Electrostatic Membrane Reflector with Composite Properties of Membrane Material - Shi, Guang Feng; Zhang, Peng (Applied Mechanics and Materials, 2013)
Membrane reflector is light enough and deployable for launching into the space for large aperture telescope. Processes of design, computation, analysis, assembly, control, and measurement of a prototype of electrostatic polyimide reflector are introduced in this paper. And, a numerical control algorithm and a measurement algorithm based on the phase-shift and incoherent imaging method are developed for this prototype. The measurement results are analyzed and the trial experience is concluded, which is very helpful for further research work in membrane reflector in the future in China.